The Efficacy of Task-Based Learning and Learning Motivation on Student’s Reading Comprehension: A Wholistic Study - Marlinton, Melisa; Syahri, Indawan; Mayasari, Santi (Elsya : Journal of English Language Studies, 2023)
This study explores the impact of Task-Based Learning (TBL) and student motivation on the reading comprehension abilities of eighth-grade students with a moderate level of English proficiency. The research aims to assess the effectiveness of TBL in improving reading comprehension outcomes and investigate the relationship between TBL, student motivation, and reading comprehension performance. The study includes sixty-four participants aged 12-14 from a public junior high school in Palembang, Indonesia. The control group receives traditional instruction, while the experimental group is taught using TBL. Pretests and posttests evaluate reading comprehension, and a questionnaire measures student motivation levels. The results reveal significant improvements in reading comprehension scores for both groups. The experimental group demonstrates an average post-test score increase of 69.88%, indicating the efficacy of TBL. While student motivation influences outcomes, no significant interaction with TBL is observed. These findings emphasize the effectiveness of TBL in enhancing reading comprehension for students with moderate English proficiency and underscore the importance of considering motivation in instructional practices. Educators can utilize these insights to enhance instructional strategies and optimize reading comprehension outcomes for similar student populations.